Representasi Citra Perempuan dalam Produk Sastra Populer Bergenre Romance pada Novel Jodoh untuk Nirmala - Adira Cahya; Nazwa Annisa; Putri Dhea Sapitri; Vita Nancy Manurung; Tomi Arianto (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes the representation of women in the novel Jodoh untuk Nirmala by Lis Susanawati using Barbara Welter’s The Cult of True Womanhood theory. The study highlights how the character Nirmala embodies the values of piety, purity, submissiveness, and domesticity as constructed within a patriarchal society. The novel reveals that women are often judged based on their virginity and domestic roles, while men are not held to the same standards. Additionally, it illustrates how patriarchy legitimizes male control over women in marriage. However, beyond portraying women as submissive to social norms, the novel also conveys a feminist message through Nirmala’s struggle to break free from patriarchal constraints. Her decision to divorce Brian represents a form of resistance against oppressive norms. Thus, the novel critiques gender inequality and emphasizes the importance of women’s freedom in determining their own lives.